Ultrastructure of the larval midgut of Bittacus planus (Mecoptera: Bittacidae) and Neopanorpa longiprocessa (Mecoptera: Panorpidae). Issue 5 (October 2017) - Liu, Lu; Hua, Bao-Zhen
Graphical abstract: Highlights: Ultrastructure of Bittacus and Neopanorpa larval midguts are compared. Infolded basal plasma membranes and lymph spaces only occur in B. planus . Longitudinal muscle bands are more compact in B. planus . Well-developed longitudinal muscles are likely related to the soil-spraying habit. Abstract: Bittacidae and Panorpidae are the two largest families in Mecoptera. The larvae of Bittacidae are different from those of Panorpidae in external morphology and habits, and have an interesting habit of spraying the body surface with soil through the anus. However, it remains unknown to date whether the larval midguts are different in structure between the two families. Here the ultrastructure of the larval midguts of the hangingfly Bittacus planus Cheng and the scorpionfly Neopanorpa longiprocessa Hua & Chou were compared using light, scanning, and transmission electron microscopy. The midguts of both species are simple tubes of single layered epithelia with digestive and regenerative cells but without diverticula. The basal plasma membrane of epithelial cells exhibits infolding in B. planus, but is closely apposed to its basal lamina in N. longiprocessa . Lymph spaces are present between adjacent epithelial cells in B. planus, but are absent in N. longiprocessa . The regenerative cells are scattered among the digestive cells in B. planus, but are aggregated in N. longiprocessa . The longitudinal muscle bands are compact in B. planus, but are sparse in N. longiprocessa . The compact longitudinal muscle bands are likely associated with their soil-spraying habit in Bittacidae.